Developing Learning Model of Basic Throw In Physical and Health Education Through Games for Second Grade Students In Central Semarang District - Selvi Atesya Kesumawati; Husni Fahritsani; Saipul Ambri Damanik (Universitas Negeri Medan, 2020)
This study aims to produce a model of basic throw through games which is useful for teachers in giving lessons to primary school students. This development model is a procedural development, because it is in accordance with the problem to be solved and the objectives to be achieved. The procedure used includes five main stages, namely: 1) conducting an analysis of the product you want to develop, 2) making an initial product of a model of basic throw through games for primary students, 3) expert validation, 4) field testing, and 5) product revision. The data are qualitative and quantitative data, while the instruments are list question and observations. Data analysis uses percentages to analyze and subject ratings to assess the feasibility, quality and acceptability of the product. The research study in a model of basic throw through games for primary students along with the development of infrastructure, regulations, and playing techniques. The model for developing basic throw through this game is proven to be feasible, of quality, then acceptable for developing the concept skills of game motion and increasing the physical fitness of primary school students, because respondents when playing ball show that the average category is quite good, meaning that this development model is average - can be demonstrated.